Teaching and learning : international best practice - McInerney, D. M. 1948-; Liem, Arief Darmanegara (Research on sociocultural influences on motivation and learning, 2008)
Our highly interconnected global education environment provides unprecedented opportunities for teaching professionals and educational researchers to share best practice in teaching and learning across international borders and sociocultural frontiers. This volume presents a diverse range of innovative educational best practices from around the world - particularly those practices that directly strengthen and enhance student motivation and achievement in a broad range of sociocultural contexts. These practices include: enhancing teaching and learning environments, particularly in relation to provision of high quality infrastructure for 21st Century (digital) learning; designing and managing after-school homework support; recruiting, developing and retaining high-quality teaching staff; promoting international and multicultural awareness through deliberate exposure to varied cultural experiences and perspectives; optimizing the benefit of project work for student academic and social outcomes; designing educational interventions based on self-concept research; and developing an international service learning course for tertiary students. The editors of the present volume have gathered over thirty renowned educators and researchers from Asia, Australia, Europe, and the United States, to share their experiences in developing best practices in teaching and learning in socioculturally and educationally diverse contexts. These practices, guided and underpinned by cutting edge educational/psychological theories and research, are believed to be adaptable to many diverse educational and sociocultural contexts. The editors invite researchers, professionals, educators, teachers, lecturers, policy-makers, and curriculum developers to think, reflect, and take action on how to utilize the underlying principles of the best practices in the present Volume to their own settings.